A linguagem enunciativa e multimodal do comunicador Chacrinha, durante a ditadura. - Cavalcanti, Maria Lígia Ramos Bezerra (2020)
The general objective of this study was to analyze the enunciative and multimodal language of the Chacrinha TV communicator, in its auditorium program broadcasted by Rede Globo, in the 1980s. It is a program broadcasted on Brazilian television during the military dictatorship under the president of João Baptista de Oliveira Figueredo when there was no freedom of expression in the country. This research shows its relevance because it is a linguistic analysis in statements considered as unusual, irreverent and comical, but which, at the same time, were coated with implicit semantic aspects and multimodal features. This time, we made an analysis of the language of the communicator Chacrinha in four of his programs broadcasted on Rede Globo television: the first program 'Casino do Chacrinha', recorded in 1982 and the others in 1985 , 1987 and the last program in 1988, in order to identify the deictic elements. personalities of Chacrinha language; to analyze the enunciative and multimodal aspects of Chacrinha's speech and to describe the multimodal aspects of the presenter's language using the enunciative approach of Émile Benveniste's theory (2005, 2006). In addition to the studies of the multimodality of David McNeill (1985, 1992) under the indissoluble gaze of oral and sign language. The nature of this research is qualitative of the documentary type, since a new analytical treatment was given to eight recordings of a television program. The methodology used to meet the desired objectives was accomplished through the audiovisual transcription of the selected programs, through the identification of the deictic elements of language, as well as the multimodal aspects of the gesture-speech relationship presented as the same meaning matrix. Thus, this research not only contributed to the enunciative and multimodal studies in the field of Language Sciences, but was also socially relevant regarding the language analysis of a communicator, remembered until today as a milestone in the history of Brazilian television, in a time of cultural and social repression.